A hybrid multi-start simulated annealing algorithm for the dynamic facility layout problems - (:unkn) unknown (Computers and Industrial Engineering, 2014)
The dynamic facility layout problem (DFLP) is associated with the arrangement of departments through more than one period. In each period, movement of materials between the departments causes the total flow cost. According to dynamic aspect of the problem, layout of the departments can be rearranged at each period paying some fixed costs. Therefore, the problem is to find the best layouts of the departments over the planning horizon minimizing the sum of total flow cost and total rearrangement cost. Due to the NP-hardness of the problem, heuristic and meta-heuristic methods have been widely used to deal with DFLP. In this study, a hybrid multi-start simulated annealing algorithm is proposed to obtain good solutions to DFLP. Effectiveness and efficiency of the proposed algorithm are compared with the algorithms in the literature.
Keywords: Dynamic facility layout; Hybrid meta-heuristics; Multi-start simulated annealing